THE EFFECT OF INTERNAL AUDIT ON FRAUD PREVENTION AT PT POS INDONESIA - Muhtadin Mubin; Teddy Rustandy; Muhammad Arya Lokamandala; Ihsan Nasihin (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
To be able to manage and manage company assets efficient, then management requires the function or role of checking diamonds or more known as internal audit. In addition, to get company property / wealth from cheating. Fraud is something that must be prevented by the company so that it does not happen, for that role is needed internal audit in saving company assets from fraud. This research tries to Knowing the implementation of internal audits, overcoming fraud (fraud), and the role of the audit internal fraud preven/tion efforts (Fraud) at PT Pos Indonesia (Persero) Office Center of Bandung. The method used in this research is survey method. Analysis Descriptive data of research results using continuum analysis. Data analysis using contrary to Product Moment. Hypothesis testing using t test. Based on test results Obtained from the conclusion that the implementation of internal audit is good, and the conclusion cheating (fraud) is good. The results of the audit assessment coefficient values when internal with variables overcoming fraud (fraud) of 0.583, included in the category of